2023
DOI: 10.1186/s13046-023-02744-8
|View full text |Cite
|
Sign up to set email alerts
|

rWTC-MBTA: autologous vaccine prevents metastases via antitumor immune responses

Abstract: Background Autologous tumor cell-based vaccines (ATVs) aim to prevent and treat tumor metastasis by activating patient-specific tumor antigens to induce immune memory. However, their clinical efficacy is limited. Mannan-BAM (MB), a pathogen-associated molecular pattern (PAMP), can coordinate an innate immune response that recognizes and eliminates mannan-BAM-labeled tumor cells. TLR agonists and anti-CD40 antibodies (TA) can enhance the immune response by activating antigen-presenting cells (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In our preceding study, in a colon carcinoma preclinical mouse model, compared to control or injecting irradiated whole tumor cells alone, we found that subcutaneous injection of the rWTC-MBTA vaccine (irradiated whole tumor cells mixed with MBTA) caused a substantial decrease in tumor volumes and improved overall survival ( 199 ). In one of our recently published manuscripts, we demonstrated that the rWTC-MBTA vaccine effectively inhibited the metastasis and impeded the growth of tumors in animal models of both breast cancer and melanoma ( 202 ). Additionally, in a therapeutically mimicking postoperative model of breast cancer, it prevented the metastasis of residual tumors and extended the survival ( 202 ).…”
Section: Application Of Tlr Agonists As Adjuvants Of Cancer Vaccinementioning
confidence: 99%
See 3 more Smart Citations
“…In our preceding study, in a colon carcinoma preclinical mouse model, compared to control or injecting irradiated whole tumor cells alone, we found that subcutaneous injection of the rWTC-MBTA vaccine (irradiated whole tumor cells mixed with MBTA) caused a substantial decrease in tumor volumes and improved overall survival ( 199 ). In one of our recently published manuscripts, we demonstrated that the rWTC-MBTA vaccine effectively inhibited the metastasis and impeded the growth of tumors in animal models of both breast cancer and melanoma ( 202 ). Additionally, in a therapeutically mimicking postoperative model of breast cancer, it prevented the metastasis of residual tumors and extended the survival ( 202 ).…”
Section: Application Of Tlr Agonists As Adjuvants Of Cancer Vaccinementioning
confidence: 99%
“…In one of our recently published manuscripts, we demonstrated that the rWTC-MBTA vaccine effectively inhibited the metastasis and impeded the growth of tumors in animal models of both breast cancer and melanoma ( 202 ). Additionally, in a therapeutically mimicking postoperative model of breast cancer, it prevented the metastasis of residual tumors and extended the survival ( 202 ). Our results also demonstrated that the rWTC-MBTA vaccine effectively prevented the growth of autologous tumors but rendered ineffective against allogeneic tumors ( 202 ).…”
Section: Application Of Tlr Agonists As Adjuvants Of Cancer Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] This vaccine strategy inhibited tumor growth in the CT26‐colon carcinoma model, an immunologically “hot” tumor model, [ 21 , 22 ] and also prevented early metastasis in preclinical models. [ 23 ] However, it is still unknown whether this strategy can treat immunologically “cold” tumors such as GBM, considering the specialized immune microenvironment in the brain. [ 24 ] Also, the detailed effects of the rWTC‐MBTA vaccine on DC subsets and TME have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%